Pengaruh Economic Value Added dan Market Value Added terhadap Harga Saham pada Perusahaan yang Terdaftar Di Jakarta Islamic Indeks - Rizqia Nur Afifah; Mochamad Edman Syarief; Intan Nurrachmi (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to examine the effect of Economic Value Added and Market Value Added on stock prices in companies listed on the Jakarta Islamic Index (JII). The type of data used is quantitative data sourced from the official website of the Indonesia Stock Exchange (IDX). The number of samples of 16 companies that meet the research criteria using purposive sampling method. Data collection uses non-participant observation method for documents in the form of company annual financial reports. The data analysis technique used is multiple linear regression analysis. The results showed that simultaneously EVA and MVA had significant effect on stock prices. Then, partially, both the EVA and MVA variables have effect on stock prices.